2018
DOI: 10.1155/2018/5939015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Changes in Cariogenic Bacteria in a Young Moroccan Population with Fixed Orthodontic Appliances

Abstract: Fixed orthodontic appliances hinder the maintenance of proper oral hygiene and result in dental plaque accumulation. Many studies report that qualitative changes in the dental flora occur after initiating the orthodontic treatment, but there is a paucity of literature on the same topic among Moroccan orthodontic patients. The aim of this study was to evaluate the changes of the oral microbial flora during the orthodontic treatment period of a young Moroccan population. Materials and Methods. Dental plaque samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Excessive bleeding and inflammation worsen the periodontal health resulting in surveillance of noticeable raise in plaque and gingival index of test group. Three months after placement of fixed appliances there was foremost augment in clinical and microbial characteristics, comparable outcomes shown by Marda et al 17 Undoubtedly, the CPITN score of orthodontic and non orthodontic groups were contradicting, admitting the fact that score for group using interdental brush were lower as compared to the ones not using brushing. Since orthodontic appliances placement hinder maintenance of proper oral hygiene causing deposition of plaque leading to increase in pocket depth, which directly contributes to increase in CPITN score and the same observation reported by Nasir et al 18 As reported by Angelina et al, 19 the most affected area periodontally in orthodontic patient is the interdental area which agrees with the observation of this study.…”
Section: Discussionsupporting
confidence: 69%
“…Excessive bleeding and inflammation worsen the periodontal health resulting in surveillance of noticeable raise in plaque and gingival index of test group. Three months after placement of fixed appliances there was foremost augment in clinical and microbial characteristics, comparable outcomes shown by Marda et al 17 Undoubtedly, the CPITN score of orthodontic and non orthodontic groups were contradicting, admitting the fact that score for group using interdental brush were lower as compared to the ones not using brushing. Since orthodontic appliances placement hinder maintenance of proper oral hygiene causing deposition of plaque leading to increase in pocket depth, which directly contributes to increase in CPITN score and the same observation reported by Nasir et al 18 As reported by Angelina et al, 19 the most affected area periodontally in orthodontic patient is the interdental area which agrees with the observation of this study.…”
Section: Discussionsupporting
confidence: 69%
“…The use of orthodontic appliances increases the risk of developing caries and gingivitis, as these devices retain plaque and both conditions are bio- film-dependent. Several authors have reported that the use of orthodontic appliances causes an increase in the count of cariogenic microorganisms, such as Lactobacillus species [3,6,19,20]. Therefore, the present study was carried out using participants undergoing orthodontic treatment who had gingivitis and visible plaque at the baseline in order to justify the use of an antimicrobial toothpaste.…”
Section: Discussionmentioning
confidence: 99%
“…All this predisposes to decrease the pH in the dental biofilm and in the presence of carbohydrates in patient`s diet, a physical barrier is formed that disturbs remineralization with the calcium and phosphate ions from the saliva (7,8). All these changes in the oral ecosystem help to increase the levels of S. mutans and Lactobacillus spp., mainly around the adhesives that fix the orthodontic appliances (9).…”
Section: Discussionmentioning
confidence: 99%